5-Hydroxymethylcytosine (5hmC) and Ten-eleven translocation 1–3 (TET1–3) proteins in the dorsal root ganglia of mouse: Expression and dynamic regulation in neuropathic pain. (3rd April 2017) - Chamessian, Alexander G.; Qadri, Yawar J.; Cummins, Matthew; Hendrickson, Michele; Berta, Temugin; Buchheit, Thomas; Van de Ven, Thomas
Abstract: Epigenetic mechanisms are increasingly implicated in chronic pain pathology. In this study, we demonstrate that the novel epigenetic mark 5-hydroxymethylcytosine (5hmC) is present in dorsal root ganglia (DRG) neurons and glia, and its levels increase following nerve injury. Furthermore, we show that the 5hmC-generating Ten-eleven translocation 1–3 (TET1–3) proteins are expressed in a cell-type specific manner in the DRG, with Tet3 displaying differential upregulation after injury, suggesting a potential role in neuropathic pain.